Explaining production expansion decisions of Dutch dairy farmers. (1st March 2016) - Samson, Gerlinda S.; Gardebroek, Cornelis; Jongeneel, Roel A.
Highlights: We analyse factors determining milk production expansion by Dutch dairy farmers. A conceptual framework combines economic, environmental and social variables. A dynamic RE probit model is used to estimate production expansion behaviour. Milk price and price volatility did not influence production expansion. Smaller farms have a higher chance to expand in production than bigger farms. Abstract: The abolition of dairy quotas in Europe in 2015 has been accompanied by uncertainty on expansion of the European dairy sector. Whereas the total amount of quotas was limited and the value of quotas was falling before 2015, a significant part of active Dutch dairy farmers followed an expansion strategy in the recent past. Therefore, it was expected that the overall milk production in the Netherlands will substantially increase after abolishment of the quota. The objective of this study is to analyse which factors determine milk production expansion by Dutch dairy farmers. A conceptual model is developed that shows how policies, market conditions, and farmers' values and goals affect their expansion decisions. This conceptual model shows that not only economic, but also social and environmental variables are important factors in expansion decisions of Dutch dairy farmers. Zooming in on the dynamic decision making process itself, we combine three investment theories to explain investment decisions. This framework is the basis for a dynamic random effects probit model that is used to estimate the effects of various economic, environmental and farm structural factors on farmers' expansion behaviour. Data is obtained from the Dutch Farm Accountancy Data Network (FADN) covering the period 2001 through 2010, with 1390 observations on 354 dairy farms included in the sample. The results show that production intensity matters when analysing production expansion behaviour of Dutch dairy farms. Compared to extensive farms, intensive farms have a higher probability for milk production expansion. The availability of land however is an important precondition. Production diversification, which is usually found at extensive farms, decreases the probability for milk production expansion. Although the findings do not directly show an increase in milk production during the sample period (farmers still respected their quota limits), the results indicate that Dutch dairy farms can potentially increase milk production in the future. In 2010 farms underutilized their stable space, as the occupancy of stable space was 71%. After milk quota abolishment farms can therefore increase livestock herd and milk production with limited investments.